2022
DOI: 10.1002/pc.26751
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chemical treatment and fiber loading on various properties of Bauhinia vahlii bast fibers/acrylonitrile butadiene styrene composites for automotive body parts

Abstract: Currently, automobile industries are paying more attention on fabricating light weight materials for making vehicle body parts. So lots of research work is been carried out on natural fibers owing to their light weight and eco-friendly nature. In this current research, composites were fabricated by reinforcing treated Bauhinia vahlii bast fiber (BV) fibers with Acrylonitrile butadiene styrene (ABS) thermoplastic polymer for making light weight automobile parts. Various properties like static and dynamic mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Similarly, the AT-BNF/ABS composites mentioned in the study by Kusić et al 32 exhibited a decrease in Charpy impact strength. Likewise, the impact strength of AT-BVF/ ABS composites, as referenced in the study by Sahu et al 33 also experienced a decline. Similarly, it is observed that in this study also the impact strength of BF/r-ABS composites is lower than the matrix r-ABS.…”
Section: Mechanical Propertiesmentioning
confidence: 88%
See 1 more Smart Citation
“…Similarly, the AT-BNF/ABS composites mentioned in the study by Kusić et al 32 exhibited a decrease in Charpy impact strength. Likewise, the impact strength of AT-BVF/ ABS composites, as referenced in the study by Sahu et al 33 also experienced a decline. Similarly, it is observed that in this study also the impact strength of BF/r-ABS composites is lower than the matrix r-ABS.…”
Section: Mechanical Propertiesmentioning
confidence: 88%
“…The said increased trend for flexural strength is observed for the BBF/CF-ABS composites as compared to the matrix CF-ABS. 15 Again Kusic et al 32 and Sahu et al 33 also addressed in their study of AT-BNF/ ABS composites regarding the increased flexural properties with the incorporation of bamboo natural fiber into the matrix in an increasing order upto 30%. 4 approximately 16.8%, 40% and 53% lower notched Izod impact strength.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…Reduced health risks and better mechanical properties are the reasons for considering bast fibers as the best fit for automotive applications. [194][195][196] Most of the European vehicle parts have been incorporated with bio-based composites. Door cladding, seatback linings, and floor panels are the major parts where the fibers are used.…”
Section: Applicationsmentioning
confidence: 99%
“…This sector uses the bast fiber with the thermoplastic and thermoset resins in the molding process to fabric the composites perfectly. Reduced health risks and better mechanical properties are the reasons for considering bast fibers as the best fit for automotive applications 194–196 . Most of the European vehicle parts have been incorporated with bio‐based composites.…”
Section: Applicationsmentioning
confidence: 99%